The Meaning of Breastfeeding Social Support Among Banjar Mothers - Dina Aprilia; Afra Hafny Noor; Retno Hanggarani Ninin; Zahrotur Rusyda Hinduan (Fakultas Dakwah dan Ilmu Komunikasi UIN Antasari Banjarmasin, 2026)
Abstract: Social support is a crucial factor influencing the success of breastfeeding practices, particularly during the postpartum period, which is characterized by physical and psychological vulnerability. However, the meaning attributed to such support is strongly shaped by the local cultural context. This study aimed to explore in depth the meaning of breastfeeding social support among Banjar mothers within their cultural setting. This study employed a qualitative approach using a grounded theory strategy as part of a mixed-method exploratory sequential design. Data were collected through in-depth interviews with 15 Banjar breastfeeding mothers selected purposively based on the principle of data saturation, and were analyzed using thematic coding through the stages of open, axial, and selective coding with the assistance of NVivo software. The findings revealed that social support is understood as a multidimensional construct, encompassing emotional support as a source of reassurance, instrumental support as practical assistance, informational support as a source of knowledge, and normative support that may be ambivalent in the form of social pressure. Social support plays a significant role in shaping the continuity of breastfeeding practices, functioning both as an enabling and constraining factor. This study contributes to the development of a conceptual understanding of social support as a culturally grounded and context-dependent construct of meaning, while also highlighting the importance of culturally sensitive approaches in maternal and child health interventions.